2021
DOI: 10.3390/bios11100387
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Optical Measurement of Aqueous Humor Glucose Levels and Correlation with Serum Glucose Levels in Rabbit

Abstract: The noninvasive measurement of serum glucose levels has been investigated for the monitoring of blood sugar control in diabetes. In our study, we aimed to develop a novel noncontact glucometer (NCGM) utilizing an optical approach to measure the intraocular aqueous humor glucose levels in the anterior chamber of rabbit eyes. The NCGM consists of a hybrid optical system that simultaneously measures near-infrared absorption and the polarized rotatory distribution of glucose molecules in the aqueous humor. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Given this consistent ratio between aqueous humor and blood glucose, we can utilize the NCGM to determine serum glucose levels in humans. Our laboratory has previously demonstrated that NCGM readings show a strong correlation with aqueous humor and blood glucose levels in rabbits, with an average aqueous humor to blood glucose ratio of 0.82 before the glucose challenge 24 . In the current study with human participants, the NCGM measurements demonstrated strong predictive accuracy for blood glucose levels (ICC>0.9 with P<0.001).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Given this consistent ratio between aqueous humor and blood glucose, we can utilize the NCGM to determine serum glucose levels in humans. Our laboratory has previously demonstrated that NCGM readings show a strong correlation with aqueous humor and blood glucose levels in rabbits, with an average aqueous humor to blood glucose ratio of 0.82 before the glucose challenge 24 . In the current study with human participants, the NCGM measurements demonstrated strong predictive accuracy for blood glucose levels (ICC>0.9 with P<0.001).…”
Section: Discussionsupporting
confidence: 56%
“…Our laboratory has previously demonstrated that NCGM readings show a strong correlation with aqueous humor and blood glucose levels in rabbits, with an average aqueous humor to blood glucose ratio of 0.82 before the glucose challenge. 24 In the current study with human participants, the NCGM measurements demonstrated strong predictive accuracy for blood glucose levels ( with ). The correlation between NCGM and SMGB at various time points was also high ( with ).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations